2012
DOI: 10.1089/brain.2012.0077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on the Structure of Functional Connectivity Networks During Episodic and Working Memory Demand

Abstract: The aim of the study was to investigate age-related differences in large-scale functional connectivity networks during episodic and working memory challenge. A graph theoretical approach was used providing an exhaustive set of topological measures to quantify age-related differences in the network structure on various scales. In a single session, 10 young (22-30 years) and 10 senior (62-77 years) subjects performed an episodic and a working memory task during functional magnetic resonance imaging. Networks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…For example, it has been demonstrated that both DMN and CEN functional correlations were greatly reduced in aging during a semantic-decision task and that these reductions were associated with cognitive decline [ 18 ]. Another study investigating functional connectivity in the aging brain showed expanded distribution of brain activity during a working memory task, with changes specifically focused on frontal-parietal connectivity [ 52 ]. This recruitment of additional resources has been demonstrated specifically during the 1back working memory task in an elderly population [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that both DMN and CEN functional correlations were greatly reduced in aging during a semantic-decision task and that these reductions were associated with cognitive decline [ 18 ]. Another study investigating functional connectivity in the aging brain showed expanded distribution of brain activity during a working memory task, with changes specifically focused on frontal-parietal connectivity [ 52 ]. This recruitment of additional resources has been demonstrated specifically during the 1back working memory task in an elderly population [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This frontal connectivity dysfunction implies impaired bifrontal, frontoparietal, and frontostriatal connections [90–92]. Toepper and colleagues, for example, used fMRI during a spatial working memory task and found a more diffuse connectivity pattern in older compared to younger adults [93] indicating less specific representations and neural circuits [94, 95]. Moreover, older adults showed reduced functional connectivity between dorsolateral prefrontal and orbitofrontal cortices associated with a disproportional accuracy decline on the behavioral level.…”
Section: Neurocognitive Changes Associated With Normal Agingmentioning
confidence: 99%
“…However, findings of age-related decreases in connectivity in parietal regions are not universal. For example, Matthaus et al found that, networks engaged during memory tasks showed increased parietal connectivity in older adults ( Matthaus et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%